2019
DOI: 10.1111/ejss.12727
|View full text |Cite
|
Sign up to set email alerts
|

Is aided phytostabilization a suitable technique for the remediation of tailings?

Abstract: Mining activity in Cartagena‐La Union mining district (SE Spain) dates back more than 2500 years. Consequently, large amounts of sterile materials with large metal(loid) contents (mostly Zn and Pb) have accumulated in tailings ponds. A reclamation strategy based on aided phytostabilization was carried out to reclaim one tailings pond to reduce environmental and public health hazards. The main goal of this study was to determine the effectiveness of the aided phytostabilization strategy after 30 months from its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…However, increased concentrations of TE may impair plant growth and weaken the success of the method [ 1 , 6 ]. Phytostabilisation can hence be supported through the addition of amendments, aiming at further reducing TE bioavailability, while improving soil quality and plant’s growth [ 7 ]. Among the available amendments, microbial inoculants and in particular arbuscular mycorrhizal fungi (AMF), able to develop symbiotic associations with most of the terrestrial plants, have long been described for their contribution towards an improved plants’ fitness in agroecosystems [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, increased concentrations of TE may impair plant growth and weaken the success of the method [ 1 , 6 ]. Phytostabilisation can hence be supported through the addition of amendments, aiming at further reducing TE bioavailability, while improving soil quality and plant’s growth [ 7 ]. Among the available amendments, microbial inoculants and in particular arbuscular mycorrhizal fungi (AMF), able to develop symbiotic associations with most of the terrestrial plants, have long been described for their contribution towards an improved plants’ fitness in agroecosystems [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of metal(loid)s in the studies soils (Table 1) exceeded in all cases the toxicity levels for soils (Table 2). The establishment of sampled specimens in soils, with concentrations of trace elements above toxicity levels, may be due to the fact that these species are resistant, because they do not translocate the metal present in their rhizosphere, called phytostabilizer plants (Martı ´nez-Martı ´nez et al, 2019;Parra et al, 2016), or because they absorb them but it does not affect them (Behmer et al, 2005;Conesa et al, 2006;Lam et al, 2018). However, it is likely that plants can grow in these soils because the labile Metals and arsenic concentrations toxic to plant growth and in leaf tissues (Kabata-Pendias, 2001;Mendez and Maier, 2008) b Metal and arsenic levels tolerable for cattle (NCR, 2005) fractions present in the soil are below those limits.…”
Section: Accumulation In Vegetal Tissues and Toxicity For Faunamentioning
confidence: 99%
“…In addition, most of the plant species took up small amounts of metal(loid)s or concentrated those that they did take up in their root systems. Martínez‐Martínez et al () concluded that their amendments were successful in transforming the low‐productivity soil into one that would support a thriving soil ecological system, which in turn enhanced phytostabilization of the contaminants at the study site. This would, in turn, provide benefits to human health.…”
Section: Special Section Contentsmentioning
confidence: 99%